2023
DOI: 10.3389/fpubh.2023.1038694
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of hypertension and type 2 diabetes: prevalence and associated factors among Haramaya University employees in Eastern Ethiopia

Abstract: BackgroundBoth hypertension (HTN) and diabetes are public health concerns in low- and middle-income countries, particularly in sub-Saharan African countries. The co-occurrence of HTN and diabetes is associated with an increased risk of mortality, morbidity, and reduced productivity in the working force. In Ethiopia, there is limited evidence on the co-occurrence of HTN and type 2 diabetes (T2DM). Therefore, this study was conducted to assess the co-occurrence of HTN and T2DM and their associated factors among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…found that serum copper levels within a certain range may be associated with elevated blood pressure. 37 Given that the co‐occurrence of hypertension and diabetes was prevalent among the adults, 38 this study aimed to explore the association between serum copper concentration and the prevalence of diabetes among hypertensive adults using the NHANES database.…”
Section: Discussionmentioning
confidence: 99%
“…found that serum copper levels within a certain range may be associated with elevated blood pressure. 37 Given that the co‐occurrence of hypertension and diabetes was prevalent among the adults, 38 this study aimed to explore the association between serum copper concentration and the prevalence of diabetes among hypertensive adults using the NHANES database.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the global health significance of co-morbid hypertension and diabetes 2 , this review incorporates papers from across various continents. Asia and America (including North and South America) are the primary contributors to this review, with United States of America 23 , 24 , 26 , 27 , 30 , 38 , 42 and India 29 , 31 , 41 , 44 , 46 contributing the most studies, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The co-occurrence of hypertension and diabetes is a serious public health burden. 1 , 2 Globally, co-morbidity is alarmingly prevalent, with statistics estimating that over 40% of patients with diabetes also suffer from hypertension. 1 , 3 This dual burden is especially apparent in older persons, underlining the challenges posed by an aging population.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations